Availability of urinary albumin measurement in Southern Brazilian laboratories - Ariana Aguiar Soares; Amanda Veiga Cheuiche; Alexandre Sauer da Silva; Larissa Petermman Jung; Joiza Lins Camargo; Sandra Pinho Silveiro (Clinical and Biomedical Research, 2015)
Introduction: Diabetic kidney disease (DKD) is the leading worldwide cause of end-stage renal disease. The current recommendation is to screen for DKD by evaluating estimated glomerular filtration rate (eGFR) and measuring urinary albumin (UA) levels in a spot sample. The aim of this study was to evaluate the availability of UA measurement in Southern Brazilian laboratories.